Fostering Collaborative Learning through Presentation, Practice, and Production: Innovative Techniques for Teaching Grammar - Ryan Purnomo; Giyoto Giyoto; Ganal Arief Rahmawan; Evi Mahsunah (STKIP Yapis Dompu, 2023)
In the method of Foreign Language Teaching, Presentation-Practice-Production (PPP) is used to teach language structures (grammar). The presentation phase is controlled by the lecturer by asking students to make presentations in groups. During the practice phase, learners practice speaking or writing the language structure correctly. Practice activities include drills, multiple-choice exercises, gap-fill exercises, and cue exercises. In this phase, the lecturer's role is to provide positive feedback to students, correct mistakes, and model the correct forms. In the production phase, learners have fully mastered the form and have learned how to produce oral and written texts. This research aims to develop a grammar teaching strategy in Collaborative Learning by employing PPP and some alternative techniques for fourth-semester students in the English Department at Universitas Nahdlatul Ulama Sidoarjo. The study employs action research with two cycles. The research findings show an improvement in students' average grammar scores, from 46.22 in the preliminary study to 71 in the first cycle and 81 in the second cycle. Furthermore, the results of the study indicate that students were enthusiastic and active in the teaching and learning process.